Aeromonas hydrophila induced necrotizing fasciitis following laparoscopic cholecystectomy - Taimoor Khalid Janjua,; Saba Siddique,; Mohammad Faisal Ibrahim,; Muhammad Nadeem Khurshaidi, (Journal of the Pakistan Medical Association, 2024)
Necrotizing fasciitis [NF] is a multifaceted disease of the muscle fascia and body tissues which demands the earliest intervention. Past reviews have documented very few cases of Aeromonas Hydrophila [AH] induced NF following abdominal surgery. AH can cause fatal NF as seen in a 72 year old female patient reported at Liaquat National Hospital &Medical College; a tertiary care center in Karachi, Pakistan on 2nd April, 2022. She had a known comorbidity of hypertension and presented with the chief complaint of symptomatic gallstones for which she underwent Laparoscopic Cholecystectomy (LAPCHOL). She developed NF of the lower abdomen post-operatively. Following uneventful Laparoscopic Cholecystectomy our patient presented to the ER two days later with severe lower abdominal pain and overlying cellulitis. Fasciotomy revealed extensive myonecrosis with necrotizing soft tissue infection. ---Continue